THE PSYCHOMETRIC PROPERTIES OF A RUSSIAN VERSION OF THE DISEASE-SPECIFIC LUPUSQOL QUESTIONNAIRE ASSESSING THE HEALTH-RELATED QUALITY OF LIFE IN PATIENTS WITH SYSTEMIC LUPUS ERYTHEMATOSUS - E. A. Aseeva; L. D. Vorobyeva; S. K. Solovyev; V. N. Amirdzhanova; S. I. Glukhova; G. M. Koilubaeva; M. V. Letunovich (Научно-практическая ревматология)
Objective: to assess the reliability, validity, and sensitivity of a Russian version of the LupusQol questionnaire.Subjects and methods. The investigation enrolled 328 patients aged 18 years or older with systemic lupus erythematosus (SLE) who met the 2012 Systemic Lupus International Collaborating Clinic (SLICC) criteria. Two tools, such as the 36-item Short-Form Health Survey (SF-36) questionnaire and LupusQol questionnaire filled out by the patients, were used to study their health-related quality of life (HRQOL). Activity was estimated using the Systemic Lupus Erythematosus Disease Activity Index 2000 (SLEDAI-2K); irreversible organ damages were evaluated by the SLICC damage index (DI). Reliability evaluation included a study of the reproducibility and internal consistency of the index. Reproducibility was evaluated using the test-retest analysis; the internal consistency was measured by calculating Cronbach’s alpha; the sensitivity was assessed by the changes in the questionnaire domains during standard therapy for SLE. Construct validity was determined in two ways: by using the known-groups method and factor analysis; criterion validity was measured by assessing the relationship with the external criteria (SF-36).Results and discussion. A total of 108 SLE patients were included to assess the reliability of the questionnaire. The results of assessing the reproducibility of the LupusQol questionnaire by the test-retest analysis showed no significant differences between the initial and repeated measures on all 8 LupusQol domains (p > 0.05). The value of Cronbach’s alpha ranged from 0.8 to 0.9 for each of the 8 questionnaire domains. After 12 months of standard therapy, 128 patients included in the assessment of questionnaire sensitivity showed a significant improvement in HRQOL for all questionnaire domains. The most significant positive changes were achieved on the domains of pain (p = 0.002), intimate relationships (IR; p=0.01), body image (p=0.0003), and fatigue (p=0.006).Validity was assessed in 328 patients with SLE. Construct validity was assessed by comparing the domains of the LupusQol and SF-36 questionnaires. A correlation (r > 0.4) was found on all the 8 LupusQol domains: physical functioning (PF), role-physical functioning (RPF), general health (GH), viability (V), social functioning (SF), and role-emotional functioning (REF) of the SF-36 questionnaire. The factor analysis of the LupusQol questionnaire revealed a satisfactory ratio of the distribution of its questions to its domains and a high correlation between the domains and its factor. Criterion validity was evaluated by comparing the LupuQol domains in 4 groups: 1) SLEDAI-2K < 4; 2) SLEDAI-2K ≥4; 3) SLICC DI = 0; 4) SLICC DI ≥1. Significant differences were found between the active SLE (SLEDAI-2K >4) group and inactive SLE (SLEDAI-2K <4) group on the domains of PF, pain, planning, IR, dependence, and body image (p=0.07, p=0.007, p=0.0004, p=0.03, and p=0.007, respectively). Significantly lower HRQOL scores were observed in patients with irreversible organ damages.Conclusion. The Russian version of the disease-specific LupusQol questionnaire is a valid, reliable, and sensitive tool assessing HRQOL in SLE patients, which has good psychometric properties.